Eosinophil-derived neurotoxin: a novel biomarker for diagnosis and monitoring of asthma - Kim, Chang-Keun (The Korean Pediatric Society, 2013)
Asthma is associated with increased levels of eosinophils in tissues, body fluids, and bone marrow. Elevated levels of eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) have been noted in asthma patients. Higher levels of EDN and ECP are also associated with exacerbated asthmatic conditions. Thus, EDN, along with ECP, may aid the diagnosis and monitoring of asthma. Several groups have suggested that EDN is more useful than ECP in evaluating disease severity. This may partially be because of the recoverability of EDN (not sticky, 100% recovery rate), as ECP is a sticky and more highly charged protein. In terms of clinical utility, EDN level is a more accurate biomarker than ECP when analyzing the underlying pathophysiology of asthma. As a monitoring tool, EDN has shown good results in children with asthma as well as other allergic diseases. In children too young to fully participate in lung function tests, EDN levels may be useful as an alter native measurement of eosinophilic inflammation. EDN can also be used in adult patients and in multiple specimen types (e.g., serum, sputum, bronchoalveolar lavage fluid, and nasal lavage fluid). These results are repeatable and reproducible. In conclusion, EDN may be a novel biomarker for the diagnosis, treatment, and monitoring of asthma/allergic disease.